A New Proposition of Business Model Innovation: Anteceding Managerial Competencies - Lejla Turulja; Selma Smajlović (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Knowledge, competencies, and human capital are the cornerstones of business innovation. Generating innovation alone is not a guarantee of success in the market, but it is necessary to successfully manage innovation, which requires managers' expertise and specific competencies. The paper focused on analyzing the impact of several managerial competencies on improving the new proposition dimensions of the business model innovation. The business model innovation consists of new creation innovation, new proposition innovation, and value capture innovation. This paper analyses the new proposition innovation segment that relates to solutions for customers and how they are offered; it consists of the dimensions of new offerings, new customers and markets, new channels, and new customer relationships. The research was conducted among managers of companies from several industries, who evaluated their competencies, namely analytical and innovative, their ability to recognize opportunities, their tenacity, and passion for work, as well as new proposition innovation of business model innovation. The findings suggest that each of the managerial competencies is influential in some way but that they do not all affect each dimension of a new proposition of business model innovation.
Keywords: O32; M1; 330; managerial competencies; business model innovation; the new proposition